Synthesis of Fluorophores that Target Small Molecules to the Endoplasmic Reticulum of Living Mammalian Cells1. (26th June 2015) - Meinig, J. Matthew; Fu, Liqiang; Peterson, Blake R.
Abstract The endoplasmic reticulum (ER) plays critical roles in the processing of secreted and transmembrane proteins. To deliver small molecules to this organelle, we synthesized fluorinated hydrophobic analogues of the fluorophore rhodol. These cell‐permeable fluorophores are exceptionally bright, with quantum yields of around 0.8, and they were found to specifically accumulate in the ER of living HeLa cells, as imaged by confocal laser scanning microscopy. To target a biological pathway controlled by the ER, we linked a fluorinated hydrophobic rhodol to 5‐nitrofuran‐2‐acrylaldehyde. In contrast to an untargeted nitrofuran warhead, delivery of this electrophilic nitrofuran to the ER by the rhodol resulted in cytotoxicity comparable to the ER‐targeted cytotoxin eeyarestatin I, and specifically inhibited protein processing by the ubiquitin–proteasome system. Fluorinated hydrophobic rhodols are outstanding fluorophores that enable the delivery of small molecules for targeting ER‐associated proteins and pathways.